Effects of Foliar Applications of Selected Insecticides on Cocoa Pests and Pollinators - Ibrahim, Abdul Ghani (1990)
Cocoa plants sprayed with insecticide such as Gamma HCH,methamidophos and cypermethrin using mistblowers at weekly intervals for 20 consecutive weeks produced high number of cocoa flowers but the percentage of effective pollination was not significantly different frOm the control.The effects of insecticides on the insects varied. The population of mosquitobug, Helopeltis sP , was low but there was fluctuation with the midges, Forcipomyia spp. aphids, Aphis and mely bugs, Cataenococus spp. The emergence of midges frOm the ground traps indicated that spraying of insectiicides did not affect the breeding of the midges in the cocoa field.